An effective strategy for creating asymmetric MOFs for chirality induction: a chiral Zr-based MOF for enantioselective epoxidation. Issue 13 (11th June 2019) - Berijani, Kayhaneh; Morsali, Ali; Hupp, Joseph T.
Abstract : A simple and rapid procedure was used to prepare chiral NU-1000 as a robust Zr-based MOF without complexity. The functionalization of NU-1000 was performed by utilizing chirall -(+)-tartaric acid via solvent-assisted linker incorporation, resulting in [C-NU-1000]. A Mo-complex was immobilized onto chiral NU-1000 for enantioselective epoxidation. Abstract : Recently the construction of chiral MOFs (CMOFs) has been very challenging and complex. For the first time, we synthesized a chiral Zr-based MOF withl -tartaric acid by solvent-assisted ligand incorporation (SALI). We show that a CMOF can be postsynthetically generated by a simple method: incorporating chiral carboxylic groups on the achiral NU-1000. The post-synthesized chiral NU-1000 was used as an asymmetric support for producing a chiral catalyst with molybdenum catalytic active centers as Lewis acid sites. Enantioselective epoxidation of various prochiral alkens to epoxids by using [C-NU-1000-Mo] is comparable to that using other asymmetric homogeneous and heterogeneous catalysts, along with high enantiomeric excess and selectivity to epoxide (up to 100%). The CMOF could be reused in the styrene oxidation after five cycles without substantial deterioration in the CMOF crystallinity or catalytic performance.